2012
DOI: 10.1097/hjh.0b013e32835731dd
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II type 2 receptor mediates sex differences in mice renal interlobar arteries response to angiotensin II

Abstract: A sex-specific, nitric oxide-mediated effect via angiotensin II type 2 receptors underlies the sex differences in the response of interlobar arteries to angiotensin II. Our findings may help understanding sex differences in renal hemodynamics and blood pressure control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 46 publications
1
6
0
Order By: Relevance
“…However, the increases in U Na V observed in both males and females in response to β-Pro 7 -Ang III were not dependent on sex. These findings also corroborate our previous findings using the non-peptide AT 2 R agonist, Compound 21 [12], and substantiate our previous reports, and that of others, that the role of the AT 2 R in the renal vasculature is enhanced in females [13,15,16]. As we have discussed in detail elsewhere [1,17,18], the sex-specific role of the AT 2 R is likely attributable to direct effects of gonadal hormones and genes encoded on the sex chromosomes.…”
Section: Discussionsupporting
confidence: 92%
“…However, the increases in U Na V observed in both males and females in response to β-Pro 7 -Ang III were not dependent on sex. These findings also corroborate our previous findings using the non-peptide AT 2 R agonist, Compound 21 [12], and substantiate our previous reports, and that of others, that the role of the AT 2 R in the renal vasculature is enhanced in females [13,15,16]. As we have discussed in detail elsewhere [1,17,18], the sex-specific role of the AT 2 R is likely attributable to direct effects of gonadal hormones and genes encoded on the sex chromosomes.…”
Section: Discussionsupporting
confidence: 92%
“…Key vascular regulatory pathways are balanced towards cardioprotection in females between puberty and menopause, after which the balance shifts to become pro-hypertensive [52]. It is likely the differences between our findings and Viegas et al [51] is a factor of ageing as the rats used in this study were 12 months of age, considered to be middle age in the Sprague-Dawley where early reproductive senescence may arise [27].…”
Section: Discussionmentioning
confidence: 77%
“…Of particular interest, there are known sex differences in the response of the renal arteries to angiotensin II in young rodents. A previous study showed renal interlobar arteries from 3-month-old mice contracted significantly less to angiotensin II compared to arteries from age-matched male mice, an effect due to angiotensin type 2 receptor-mediated nitric oxide release in females [51]. Key vascular regulatory pathways are balanced towards cardioprotection in females between puberty and menopause, after which the balance shifts to become pro-hypertensive [52].…”
Section: Discussionmentioning
confidence: 99%
“…The angiotensin type 2 receptor (AT 2 R) also opposes the pressor actions of the classic Ang II/AT 1 R (12). Despite similar expression levels of the AT 2 R in male and female mice, AT 2 R blockade enhances Ang II-induced renal vasoconstriction in female mice but not in males (37). Thus, the AT 2 R may also be a potential mediator of the sex difference in acute hyperresponsiveness to acute Ang II in growth-restricted rats.…”
Section: Discussionmentioning
confidence: 94%